2022
DOI: 10.21272/mmi.2022.2-23
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Approach to Identification of Innovative Determinants of Human Capital Management

Abstract: This article summarizes the arguments and counter-arguments in the scientific discussion on identifying the essential characteristics of human capital and key quantitative indicators of its evaluation. The article determined the evolutionary patterns of changing approaches to interpreting the essence of human capital. The study's main purpose is to form an integrated indicator of human capital assessment and identify the most relevant innovative drivers and inhibitors of its development. Systematization of lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Demand has shifted from unskilled and semi-skilled workers to highly skilled (and highly paid) workers. As Safarov et al (2022) write, these changes in demand outpaced changes in supply in the same direction. Changes in demand are often driven by skill-based innovations, where products are produced more efficiently using a greater proportion of skilled and unskilled labor than before.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Demand has shifted from unskilled and semi-skilled workers to highly skilled (and highly paid) workers. As Safarov et al (2022) write, these changes in demand outpaced changes in supply in the same direction. Changes in demand are often driven by skill-based innovations, where products are produced more efficiently using a greater proportion of skilled and unskilled labor than before.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, the replacement of skilled labor occurs across sectors rather than primarily reflecting the decline of less skilled sectors. To a large extent, these technological changes are due to the spread of information and communication technologies and are not limited only to the services sector (Safarov et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cheng et al [43] noticed that green competitiveness is a development approach that foresees improving social and economic performance, resource-use indicators, and environmental quality. Scholars [44,45] have confirmed that improving a company's green competitiveness requires affordable financial and human resources with appropriate knowledge and competencies. Moreover, past studies [46] outline that stakeholders and their incorporation into making decisions significantly affect a company's green competitiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, for this to happen, it is essential to understand the interests and needs of people to motivate employee development within workplaces. For instance, Kuzior et al (2022b) found that employees from generations Y and Z left their jobs due to the lack of self-development opportunities, disagreement with the company's culture and values, or unsatisfactory relationships with their supervisors (Safarov et al, 2022). Addressing these issues is crucial for fostering a partnership approach, which is vital for human capital development (Salisu, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%